The Use of Organic Firearms of the National Police in the Defense of National Vital Objects and Certain Objects in the Jurisdiction of the Bali Police - I Made Mudasna; Ni Ketut Wiratny; Komang Edy Dharma Saputra (PT Publikasiku Academic Solution, 2025)
The use of organic firearms by the Indonesian National Police (Polri) in securing National Vital Objects (Obvitnas) and Certain Objects within the jurisdiction of Bali Regional Police (Polda Bali) is conducted in a strict and structured manner. Authorization must follow an official hierarchical process, beginning with the officer’s request and requiring approval by the Regional Police Chief (Kapolda) through the Director of Intelligence and Security (Intelkam). Requirements include a written request, assignment letter, firearm control card, and firearm passbook, along with field verification of the applicant and the condition of the weapon. Firearms may only be used in situations involving an actual threat to life, preceded by mandatory warnings and with full accountability for every action taken. Misuse of firearms is considered a serious offense, subject to administrative sanctions such as demotion or dismissal, and criminal penalties under Law No. 12 of 1951 on Unauthorized Firearm Possession and the Indonesian Penal Code (KUHP), including Articles 351, 338, and 359. Legal proceedings are conducted in general courts without exception. Strict supervision and regular evaluations are carried out to prevent misuse. Firm and transparent law enforcement is essential to maintaining professionalism and public trust in Polri.